Modifying and Integrating in vitro and ex vivo Respiratory Models for Inhalation Drug Screening - Cidem, Aylin; Bradbury, Peta; Traini, Daniela; Ong, Hui Xin (Frontiers in Bioengineering and Biotechnology, 2020)
For the past 50 years, the route of inhalation has been utilised to administer therapies to treat a variety of respiratory and pulmonary diseases. When compared with other drug administration routes, inhalation offers a targeted, non-invasive approach to deliver rapid onset of drug action to the lung, minimising systemic drug exposure and subsequent side effects. However, despite advances in inhaled therapies, there is still a need to improve the preclinical screening and the efficacy of inhaled therapeutics. Innovative in vitro models of respiratory physiology to determine therapeutic efficacy of inhaled compounds have included the use of organoids, micro-engineered lung-on-chip systems and sophisticated bench-top platforms to enable a better understanding of pulmonary mechanisms at the molecular level, rapidly progressing inhaled therapeutic candidates to the clinic. Furthermore, the integration of complementary ex vivo models, such as precision-cut lung slices and isolated perfused lung platforms have further advanced preclinical drug screening approaches by providing in vivo relevance. In this review, we address the challenges and advances of in vitro models and discuss the implementation of ex vivo inhaled drug screening models. Specifically, we address the importance of understanding human in vivo pulmonary mechanisms in assessing strategies of the preclinical screening of drug efficacy, toxicity and delivery of inhaled therapeutics.